Influence of high powder flow dynamics on the efficiency of laser-directed energy deposition - Hong Seok Kim; Sang Hu Park (Materials & Design)
The behavior of powder streams under high-flow conditions remains not fully explored, despite its critical importance for enhancing productivity in modern laser-directed energy deposition (L-DED) processes. This study visualizes powder flow dynamics using area illumination and high-speed imaging. The effects of powder feeding rate (1.5–40.2 g/min) and gas flow rate (0–7 L/min) are systematically investigated. Through image stacking, relative powder concentration and particle velocity are quantified. At low feeding rates, irregular trajectories from shallow bounce angles reduce focusing efficiency. At high feeding rates, intensified inter-particle collisions stabilize trajectories but also lower focusing efficiency due to gas flow deceleration. These findings enable identification of optimal powder–gas flow combinations. Deposition efficiency, evaluated from 42 single-track experiments, strongly correlates with focusing efficiency, though significant deviations occur under high powder flow conditions. A physics-based model is proposed to calculate powder incorporation efficiency into the melt pool as a function of feeding rate and key physical parameters—namely, the melting ratio of in-flight particles, melt pool size, and both the particle count and residence time on the melt pool surface. The results offer actionable insights for optimizing powder delivery and improving overall process efficiency in high-throughput L-DED applications.